Roadkill in a Mediterranean island: Evaluating ten-years of official records - Ioannis N. Vogiatzakis; Savvas Zotos; Vassilis Litskas; Stalo Leontiou; Marilena Stamatiou (PLoS ONE, 2025)
Roadkill is a global issue contributing to biodiversity decline which is increasingly recognized by scientists and decision-makers. In Cyprus, a biodiversity hotspot with one of the highest road densities in Europe, the impact of roads on wildlife has been largely overlooked due to the absence of life-threatening collisions. We analysed data from a 10-year roadkill dataset (2013–2022) collected systematically by the Department of Public Works across 27 main roads, primarily aimed at driver safety. Due to the absence of spatial attributes for roadkill locations, the dataset was analysed to identify taxonomic, seasonal, and temporal roadkill trends in Cyprus for the first time. A total of 1,985 roadkill incidents were recorded, involving seven wildlife taxa: foxes (44%), birds (26%), hedgehogs (11.5%), snakes (7%), hares, rats, and lizards. Most roadkill occurred in the Nicosia district (65%). Statistical analyses using chi-square tests with post-hoc Bonferroni corrections revealed strong associations between road types and taxa. Fox and bird roadkill incidents were most common on highways, while hedgehogs and snakes were frequent on secondary interurban or rural roads. Roads near protected areas exhibited higher roadkill frequencies than highways. A positive relationship between traffic volume and roadkill risk was evident, with higher traffic roads posing greater risks. Seasonal patterns showed increased roadkill during spring and summer, peaking in June. This synthesis provides crucial insights into roadkill patterns, offering guidance for conservation and mitigation actions. However, the current monitoring system, focused on driver safety, is inadequate for comprehensive roadkill reporting. Key limitations, such as the absence of spatial data and weaknesses in the protocol, have been identified, with recommendations for improvement proposed to enhance future monitoring efforts.